BREAST CANCER DIAGNOSTIC APPROACH - Khabibullo Narzullayevich, Abdullaev; Nodir Ablokulovich , Juraev; Saodat Khabibulloevna, Abdullayeva (European Journal of Life Safety and Stability (2660-9630), 2021)
According to European scientists, about 90% of newly diagnosed cancers occur in epithelial forms of cancer, among them, one of the most common is breast cancer (BC). In Western Europe, approximately 25% of breast cancers are detected in women under the age of 50. Breast cancer is less common in men and accounts for only 1% [5,8]. Mammographic screening conducted every two years in the age group from 50 to 69 years reduces the cancer mortality rate by 15%, but also increases the probability of hyperdiagnosis by 30% [4,8].